UK local authority kerbside recycling and alternative recycling methods : awareness, usage and correlations - Evans, Ross (2021)
Following the implementation of the UK’s Waste Strategy 2000 and later the implementation of EU Directive 2008/98/EC, recycling rates have improved dramatically within the UK. The expansion of this sector has created multiple avenues for households to reuse or recycle their goods. This Master’s thesis aimed to identify correlations between the awareness and usage of local authority kerbside recycling versus that of alternative recycling methods. The research questions focused on identifying awareness and usage levels of alternative recycling methods; motivations for using alternative recycling methods; correlations between local authority kerbside recycling usage and alternative recycling methods. This was a mixed methods research which entailed the distribution of 145 questionnaires. Data analysis for questionnaires was conducted through the use of SPSS and content analysis, the local authority recycling methods were examined via data published on the WasteDataFlow online platform. The results were multifaceted. Decreased awareness levels of alternative recycling methods were linked with decreased usage rates amongst those who were aware. Financial incentives did not appear to be a primary motivator for using alternative recycling methods which offered a financial incentive. People who believe they are hindered from utilising local authority kerbside recycling are also significantly less likely to use alternative recycling methods. The usage of alternative recycling methods appeared to compliment local authority kerbside recycling and did not detract from it. The range of materials collected by local authority kerbside recycling services did not impact upon the usage of alternative recycling methods.